Active film made from Psidium guajava peel and starch for use in food packaging - CARVALHO, Cleberyanne da Silva; SANCHES, Marcio Augusto Ribeiro; DELALIBERA, Priscila; TUSSOLINI, Martha; KONDA, Danilo Hiroshi; PERTUZATTI, Paula Becker; TUSSOLINI, Loyse (Food Science and Technology, 2025)
The disposal of plastic film is a global problem that generates much pollution. The full use of waste from the food industry brings numerous benefits, including sustainable practices. Using films made with natural antioxidants derived from agro-industrial waste is considered an alternative to minimize these impacts. Given this context, this study aimed to develop and characterize films based on guava (Psidium guajava) peel flour for active food packaging. The films presented low thickness and solubility in water, proving to be a barrier to water vapor and suitable for maintaining the integrity of foods added to them. Moreover, their elasticity and resistance proved to be moderate and their moisture content is high due to the presence of large amounts of phenolic compounds from guava peel flour (320.58 ± 81.1 mg gallic acid/100 g sample), resulting in clear, slightly greenish-yellow films, which present their best effect as active antioxidant packaging to be applied in alcoholic foods (36 μmol Trolox/g), followed by use in acidic foods (17.2 μmol Trolox/g). This study demonstrated the potential for applying guava residue as a raw material for producing biodegradable films, proposing a purpose for the peel of this fruit.